2012
DOI: 10.1017/s002185961200072x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of morpho-physiological traits on grain yield of sorghum grown under stress at different growth stages, and stability analysis

Abstract: SUMMARYRecent trends in climate change resulting in global warming and extreme dry spells during rainy seasons are having a negative impact on grain and fodder production in rain-fed crops in India. Understanding the mechanisms of drought tolerance at various growth stages will help in developing tolerant genotypes. Crosses were made between elite and drought-tolerant sorghums, and F2and F3progenies were evaluated for drought tolerance in multiple locations. Twenty-five F4/F5derivatives along with drought-tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In reviewing the literature on this topic in sorghum, we concluded that the studies from which substantial yield reductions were reported were characterised by imposition of water deficit for relatively long periods, usually 15 days or greater, often including lengthy dry‐down periods for stress development and often with stress extending into the reproductive stage (e.g. Inuyama et al., ; Lewis et al., ; Sankarapandian et al., ). Studies that reported yield maintenance seem to be characterised by mild water deficit stress, with varied duration and with some cultivar response differences observed (Craufurd & Peacock, ; Munamava & Riddoch, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In reviewing the literature on this topic in sorghum, we concluded that the studies from which substantial yield reductions were reported were characterised by imposition of water deficit for relatively long periods, usually 15 days or greater, often including lengthy dry‐down periods for stress development and often with stress extending into the reproductive stage (e.g. Inuyama et al., ; Lewis et al., ; Sankarapandian et al., ). Studies that reported yield maintenance seem to be characterised by mild water deficit stress, with varied duration and with some cultivar response differences observed (Craufurd & Peacock, ; Munamava & Riddoch, ).…”
Section: Discussionmentioning
confidence: 99%
“…Water deficit can negatively affect the yield of crops, including grain sorghum (Assefa, Staggenborg, & Prasad, ; Lesk, Rowhani, & Ramankutty, ). But the effects of water deficit on crop yield often have a strong interaction with the timing of the stress relative to the stage of growth of the plant and the severity of stress (Abid et al., ; Rowland et al., ; Sankarapandian et al., ). Researchers have long studied the details of this phenomenon in order to prescribe strategies to avoid or minimise yield loss (Cui et al., ; Eck & Musick, ; Munamava & Riddoch, ; Rowland et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In arid and semiarid regions, sorghum is an important source of roughage because of its morpho-physiological adaptations to the water stress that provide high dry matter yield (DMY) and adaptability in areas with uneven distribution of rainfall (Sankarapandian et al, 2013; Ahmeda et al, 2016; Rakshit et al, 2016; Su-jiang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Sorghum is an important forage crop used in livestock systems in many regions around the world because of its adaptation to different environments (Sanchez et al, 2002 ; Fonseca et al, 2012 ; Amelework et al, 2015 ). In arid and semiarid regions, sorghum is an important source of roughage because of its morpho-physiological adaptations to the water stress that provide high dry matter yield (DMY) and adaptability in areas with uneven distribution of rainfall (Sankarapandian et al, 2013 ; Ahmeda et al, 2016 ; Rakshit et al, 2016 ; Su-jiang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%